Corpus-based analysis of representations around the words PPSMI and DLP in Malaysian mainstream media, The Star - Lo, Ke Yuan (2021)
Since the National Education policy was implemented in the 1970s, the exposure to English language among Malaysians has declined and the average English proficiency among Malaysians has been deteriorating, notwithstanding the position of English language as a compulsory second language in national schools. Although there have been English reinforcement programmes such as the teaching and learning of science and mathematics in English (hereinafter PPSMI) and dual language programme (hereinafter DLP), the alarming disparity between the implementation of policies and goal attainment has been a pressing issue that lacks appropriate attachment measures. Therefore, this research sets out to examine the representation of the educational policies, PPSMI and DLP, and the similarities and differences between the representation of these two policies. The research utilizes a combination of quantitative method and qualitative methods. By adopting corpus linguistics analysis and collocational analysis, the findings uncover the positive and negative representations from the perspective of different public and mainstream media by looking at the collocates employed in the news articles of the mainstream media, The Star. Besides, the discussion of the research also offer insight into how the representation of PPSMI resembles or differs from the representation of DLP through discourse analysis and manual concordance analysis as qualitative methods.